2017
DOI: 10.1111/anu.12484
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, nutrient digestibility and lipase activity in juvenile rainbow trout (Oncorhynchus mykiss) fed fat powder in diet containing emulsifiers (cholic acid and Tween-80)

Abstract: This research was conducted to investigate the effects of two dietary emulsifiers on nutrient digestibility and lipase activity in rainbow trout (Onchorhyncus mykiss). A basal rainbow trout diet containing fat powder supplemented with 10 and 5 g kg −1 of cholic acid, and 20 and 40 g kg −1 of Tween-80. Control diet contained no emulsifiers with fat powder was replaced by fish oil. Each diet was randomly assigned to 1,500-L tanks in triplicate. Juvenile rainbow trout with an initial weight of 27.32 ± 2.03 g were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…Similarly, our result showed that the addition of 0.2 g kg −1 bile acids in feeds could significantly enhance the growth performance together with the activities of lipase and protease of shrimp, indicating that bile acids may be also capable of promoting the emul- Dietary bile acids have been reported to affect serum biochemical indexes of juvenile rainbow trout (Adhami et al, 2017). TG is the most crucial ingredients of blood lipids, which can reflect the body's lipid metabolism status to some extent.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, our result showed that the addition of 0.2 g kg −1 bile acids in feeds could significantly enhance the growth performance together with the activities of lipase and protease of shrimp, indicating that bile acids may be also capable of promoting the emul- Dietary bile acids have been reported to affect serum biochemical indexes of juvenile rainbow trout (Adhami et al, 2017). TG is the most crucial ingredients of blood lipids, which can reflect the body's lipid metabolism status to some extent.…”
Section: Discussionsupporting
confidence: 64%
“…Emulsifying property is a characteristic of PHs which varies with factors like solubility and pH level as solubility increases with rising pH by which the emulsifying activity increases (Klompong et al, ; Mutilangi, Panyam, & Kilara, ). Emulsifiers mediate mixing of fats in water leading to the formation of polar and non‐polar molecules and facilitating the effect of lipase enzyme on these molecules and improving fat digestion (Adhami, Amirkolaie, Oraji, & Kenari, ). The deficiency of bile acids in the intestine decreases the digestion and absorption of fats, especially saturated fatty acids (Ketels, ).…”
Section: Discussionmentioning
confidence: 99%
“…The gall bladder capsule of these fish was extremely fragile and easy to rupture. salts were found to improve the growth performance of rainbow trout (Adhami et al, 2017;Iwashita et al, 2008;Yamamoto et al, 2007) and turbot fed plant protein-based diets. Iwashita et al (2008) also reported that increased bile salt levels were observed in rainbow trout when cholytaurine (a bile acid) was supplemented to a plant-based diet.…”
Section: Liver Histology and Gall Bladder Morphologymentioning
confidence: 99%